DCGAN data balancing to improve accuracy of hybrid CNN-LSTM intrusion detection framework in SDN environment - Feizi-Derakhshi, Mohammad-Reza; Mutasher AL-Talebei, Watheq Ghanim (Національний технічний університет "Харківський політехнічний інститут", 2025)
Maintaining robust network security in Software-Defined Networking (SDN) systems has become increasingly challenging due to sophisticated cyber-attacks and the centralized nature of SDN. This paper introduces a novel intrusion detection system based on a hybrid deep learning model that combines Convolutional Neural Networks (CNN) for spatial feature extraction and Long Short-Term Memory (LSTM) networks for temporal dependency extraction. The approach is applied to the large InSDN dataset, having labeled traffic for normal activity as well as various classes of attacks, to train multi-class as well as binary classifiers. Synthetic samples are generated based on Deep Convolutional Generative Adversarial Networks (DCGAN) in order to effectively tackle the issues due to class imbalance and thereby enhance the detection rate for minority classes of attacks. Experimental tests carried out in a simulated SDN network with Mininet and Hping3 have outstanding performance, with the binary model achieving 99.81% accuracy and the optimal multi-class model achieving 99.4% accuracy. Such promising results demonstrate the capability of the proposed framework to offer an efficient and scalable real-time intrusion detection solution for the modern SDN infrastructures.

Підтримання надійної мережевої безпеки в системах із програмно-визначеними мережами (SDN) стає все більш складним через складні кібератаки та централізовану природу SDN. Ця робота представляє нову систему виявлення вторгнень на основі гібридної моделі глибокого навчання, яка поєднує згорткові нейронні мережі (CNN) для виділення просторових ознак та мережі довгої короткочасної пам’яті (LSTM) для виділення часових залежностей. Підхід застосовано до великого набору даних InSDN, що містить маркований трафік для звичайної активності та різних класів атак, для навчання як багатокласових, так і бінарних класифікаторів. Синтетичні зразки генеруються на основі глибоких згорткових генеративних змагальних мереж (DCGAN) для ефективного вирішення проблем через дисбаланс класів і, таким чином, підвищення рівня виявлення для менших класів атак. Експериментальні тести, проведені в імітованій SDN мережі з Mininet та Hping3, демонструють видатну продуктивність: бінарна модель досягає 99.81% точності, а оптимальна багатокласова модель – 99.4% точності. Такі перспективні результати демонструють здатність запропонованої рамки запропонувати ефективне та масштабоване рішення для виявлення вторгнень у реальному часі для сучасних SDN інфраструктур.
Балансування даних DCGAN для покращення точності гібридної CNN-LSTM системи виявлення вторгнень у середовищі SDN
Keywords: Software-Defined Networking; attacks; CNN; LSTM; DCGAN; Mininet; програмно-визначені мережі; атаки; CNN; LSTM; DCGAN; Mininet